The Effect of Nitrogen Addition in Liquid Fertilizers and Seasons on the Active Content of Epigallocatech in Gallate (EGCG) Tea Shoots (Camellia sinensis L.) - Zakarias F. M. Hukom (Faculty of Agriculture, Pattimura University, 2020)
Epigallocatechin Gallate (EGCG) is a bioactive compound derived from tea shoot catechin that posing very high antioxidant. EGCG is widely used as raw materials in therapeutic healing of various degenerative diseases. EGCG content in tea shoots is largely determined by climatic factors and cultivation technique management, especially nitrogen nutrient supply as a key element in the early stages of catechin precursor biosynthesis. This study aims to determine the effect of adding N levels in liquid and seasonal fertilizers on the active content of EGCG tea shoots. The experimental design used was a complete randomized consisting of 5 levels of fertilization in rainy and dry seasons. The results showed that the application of liquid fertilizer without the addition of N in the dry season has a significant effect on the EGCG content of tea shoots and 12,35% higher than the rainy season. The EGCG content in the dry season is 97.45% to 98.16% higher than the rainy season, and 63.73% is higher than the control plants in the dry season.